ANALISIS PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM, WORD OF MOUTH DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN FESYEN NOOR - Fitria, Aliah Noor; Christina, Christina (Universitas Ciputra Surabaya, 2023)
Noor is a clothing boutique that sells various Muslim and non-Muslim cloth with affordable price and good quality. Noor boutique is located in Bangkalan city. Noor sells and marketing through online by using Instagram, offline by opening boutique in Bangkalan city, and also through word of mouth. Noor boutique in Bangkalan city has strategic location, safe and spacious parking area. This research is done to find out the effect of Instagram social media marketing, word of mouth, and location on purchase decision of Noor fashion consumers. Data in this research amounts 168 respondents in which majority age is 18-24 years old. The population that is used is consumers who have ever shopped at Noor boutique. The sample that is chosen with non-probability sampling technique with purposive sampling method with criteria age at least 18 years old. Data that is used in this research through questionnaire is distributed online and is processed using multiple regression analysis of SPSS 25. The results of this research shows that Instagram social media marketing, word of mouth, and location affect positive on purchase decision of Noor fashion consumer.